2005
DOI: 10.1387/ijdb.051984lp
|View full text |Cite
|
Sign up to set email alerts
|

Genetic interaction of Gli3 and Alx4 during limb development

Abstract: The Gli3 and Alx4 transcriptional regulators are expressed in the anterior limb bud mesenchyme and their disruption in mice results in preaxial polydactyly. While the polydactylous phenotype of Alx4 deficient limb buds depends on SHH, the one of Gli3 deficient limb buds is completely independent of SHH signalling, suggesting that these genes act in parallel pathways. Analysis of limb buds lacking both Gli3 and Alx4 now shows that these two genes interact during limb skeletal morphogenesis. In addition to the d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
29
0
1

Year Published

2009
2009
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(32 citation statements)
references
References 29 publications
2
29
0
1
Order By: Relevance
“…This indicates that the A to T mutation in Alx4 m1Yzcm is a common result of ENU mutagenesis. The Alx4 gene, which encodes a paired-type homeodomain protein that acts as a transcriptional regulator expressed in the anterior limb bud mesenchyme, plays an important role in limb patterning (Qu et al, 1997(Qu et al, , 1998Panman et al, 2005). Alx4 loss-of-function mutations result in the lst mutant, a preaxial polydactylous phenotype with ectopic Shh expression in the anterior mesenchyme of the limb bud during development.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This indicates that the A to T mutation in Alx4 m1Yzcm is a common result of ENU mutagenesis. The Alx4 gene, which encodes a paired-type homeodomain protein that acts as a transcriptional regulator expressed in the anterior limb bud mesenchyme, plays an important role in limb patterning (Qu et al, 1997(Qu et al, , 1998Panman et al, 2005). Alx4 loss-of-function mutations result in the lst mutant, a preaxial polydactylous phenotype with ectopic Shh expression in the anterior mesenchyme of the limb bud during development.…”
Section: Discussionmentioning
confidence: 99%
“…Analysis of polydactyly mutations showed that Shh transcription is negatively regulated by several genes including Fgf, Gli3, and aristaless-like 4 (Alx4). Deficiency in Gli3, which encodes a zinc finger protein that acts as a transcription factor, leads to the extra toes (Xt) mutation, and the Alx4 is considered to be linked to the mouse mutant Strong's luxoid (Lst) Qu et al, 1998;Kuijper et al, 2005;Panman et al, 2005). During limb bud development, Alx4 becomes critical for repression of anterior ectopic Shh expression (Qu et al, 1997).…”
Section: Introductionmentioning
confidence: 99%
“…Progenitor cells in the presumptive radius area may have been distalized, because later upregulation of Shh predominantly affects the cells forming the distal limb. For instance, in the Gli3 and Alx4 double mutant, loss of the radius is observed together with polydactyly caused by ectopic Shh expression 29 .…”
mentioning
confidence: 99%
“…The identities of digits under paracrine signaling are concentration dependent. Digit 1 is not reliant on Shh, rather, a recent investigation suggests that digit 1 is specified by the interaction of the Alx4 transcription factor with Gli3 (Panman et al, 2005) (Fig. 6).…”
Section: Constraints On Digit Number and Identitymentioning
confidence: 96%
“…The knockout data suggest that genetic interactions between Shh and Gli3 define digit number and identity (Chiang et al, 2001;Litingtung et al, 2002;te Welscher et al, 2002). Top: The developing limb bud is shown with dotted ovals representing the presumptive digit-forming regions (5-4-3-2 from posterior to anterior direction) under the influence of Shh, whereas the patterning of digit-1 is under the combined regulation of Gli3 and Alx4 transcriptional factors (Harfe et al, 2004;Panman et al, 2005).…”
Section: Acknowledgmentsmentioning
confidence: 99%